How do educators in one New Zealand undergraduate Bachelor of Oral Health course teach and nurture professionalism?. (17th May 2017) - Smith, L.; Adam, L.; Moffat, S.; Meldrum, A.; Ahmadi, R.
Abstract: Introduction: Research on integrated dental hygiene and dental therapy courses is scarce; studies reporting on how staff in these combined scope courses teach professionalism are even more scarce. This study aimed to partially fill these research gaps. Method and materials: In 2016, online surveys were sent to 34 staff members who taught into the integrated Bachelor of Oral Health (BOH) course at the University of Otago's Faculty of Dentistry; 13 were returned. Two focus groups were conducted with six BOH educators. Results: Aspects of professionalism were taught and nurtured in the formal curriculum, the clinic and the informal curriculum. In the formal curriculum, policies outlining the professional standards of behaviour expected of oral health practitioners and students in New Zealand and the Faculty were discussed. In the clinic, educators taught professionalism through modelling clinical skills, assessing students' performance and commenting on their reflective logbooks. In the informal curriculum, BOH teachers nurtured professionalism through discussions about standards of behaviour outside of the university. Role modelling was the most common method that participants reported they taught or nurtured professionalism in their students. Discussion: Professionalism is a complex concept that is taught and nurtured in a number of ways over all aspects of the course. Conclusion: Oral Health educators need to maintain a high standard of professionalism when interacting with students and patients, as well as in public spaces, in order to model professionalism to their students.